Proteômica quantitativa e histologia do pericarpo de açaí (Euterpe oleracea Mart.) em desenvolvimento - Andrade, Moab Torres de (2018)
The pericarp of açaí (Euterpe oleracea Mart.) has aroused great economic and scientific interest, especially by the presence of bioactive compounds. However, information regarding the genetics of the species, as well as metabolic and histological dynamics during pericarp development are scarce. Thus, the objective of this study was the histological and quantitative proteomic analysis of the developing pericarp of E. oleracea. To this purpose, fruits were collected and grouped in 12 stages of development (E0: floral bud - E11: ripe fruit), which were submitted to histological and histochemical analysis. Such analysis demonstrated noticeable structural changes in the pericarp, such as intense cell division responsible by formation of the layers of sclerenchyma and fundamental parenchyma in the mesocarp, resulting in the stratification of the mature pericarp into four layers. In the pericarp were observed the presence of raphides, deposition in the advanced stages of lipids and subepidermal accumulation of anthocyanins. Considering these data, four stages (E3, E6, E9 and E11) were selected for proteomic analysis, with protein extraction by Tris/Phenol method, trypsin digestion (shotgun approach), isobaric labeling of peptides with the reagent iTRAQ® 4-plex, pre-fractionation of labeled peptides in HPLC equipped with HILIC column and high-performance mass spectrometer (Q-Exactive Plus) analysis. Data analysis resulted in 4286 identified proteins, of which 476 presented differential abundance between the stages (p<0.05), mostly involved in carbohydrate metabolism and secondary metabolism. It was observed that the processes of glycolysis and cellular respiration are stimulated in E3 and E11, corresponding to the moments of high cell division and ripening of the pericarp, respectively. The higher abundance at the beginning and end of the development of phenylpropanoid pathway proteins is related to the lignification, cellular expansion and accumulation of phenolic acids in the pericarp. The process of anthocyanin accumulation in the pericarp responds to the increase in abundance of the leucoanthocyanidin dioxygenase, anthocyanidin O-3-glycosyltransferase and UDP-glycosyltransferase proteins. The present work presents the main histological changes in the development of the pericarp and fills the gaps of proteomic data for E. oleracea, in order to contribute to future biotechnological improvements in this crop.